Comparative efficacy and safety of different recommended doses of telitacicept in patients with systemic lupus erythematosus in China: a systematic review and meta-analysis - Gao, Shenglan; Yang, Chunlong; Huang, Bitang; Yang, Lawei; Lu, Lu; Yang, Huiting; Li, Ting; Pan, Qingjun (Frontiers in Immunology, 2025)
BackgroundTelitacicept, a new biological agent, was approved in China for treating systemic lupus erythematosus (SLE) in 2021. Its optimal dosing for treating SLE remains unclear. Therefore, the aim of this meta-analysis is to evaluate the efficacy and safety of various telitacicept doses in SLE treatment.MethodsPubMed, EMBASE, Cochrane libraries, Web of science, China National Knowledge Infrastructure (CNKI), VIP, Wanfang, and Sinomed were searched for the controlled trials that studied the efficacy and safety of telitacicept on SLE patients from their initiation to April 30, 2024. The analysis included three randomized controlled trials (RCT) with 606 participants. We used fixed-effects models for meta-analyses and the risk ratios (RRs) and corresponding 95% confidence intervals (CIs) to evaluate the effectiveness and safety. Heterogeneity was assessed and quantified using I2.ResultsAll telitacicept dosages (80 mg, 160 mg, 240 mg) significantly improved SLE Responder Index 4 (SRI4) responses compared to the control group (RR = 2.20, 95%CI:1.50-3.21, p < 0.0001; RR = 2.18, 95%CI: 1.82-2.62, p < 0.00001; RR = 2.44, 95%CI: 1.67-3.56, p < 0.00001, respectively). The 80 mg, 160 mg, and 240 mg groups also showed better improvement on SELENA-SLE Disease Activity Index (SELENA-SLEDAI) scores (RR = 1.63, 95%CI: 1.23-2.17, p = 0.0008; RR = 1.72, 95%CI: 1.45-2.04, p < 0.00001; RR = 1.73, 95%CI: 1.30-2.30, p = 0.0002, respectively) and Physician Global Assessment (PGA) scores (RR = 1.25, 95%CI: 1.09-1.44, p = 0.002; RR = 1.39, 95%CI: 1.25-1.55, p < 0.00001; RR = 1.24, 95%CI: 1.09-1.42, p = 0.002, respectively). Furthermore, 160 mg group exhibited higher British Isles Lupus Assessment Group (BILAG) score than the control group (RR = 1.11, 95%CI: 1.01-1.22, p = 0.03). As for security, 160 mg telitacicept group had higher incidence of adverse events (AEs) than the control group (RR = 1.10, 95%CI: 1.03-1.18, p = 0.007).ConclusionTelitacicept combined with standard therapy presents potential benefits but there are certain safety concerns with certain dosages of telitacicept, warranting further investigation for optimal dosing strategies in SLE management.Systematic review registrationINPLASY.COM, identifier INPLASY202440101.